Integrated Care for Aged Parkinson’s Disease Patient: A Case Study - Thamayanthi Naidu, Manoharan; Tengku Aizan, Hamid; Asmidawati, Ashari; Rajan, Balakrishnan (INTI International University, 2023)
Few research articles emphasizing on integrated care in Parkinson’s disease with Malaysia context. Most of the researchers are focusing on the non-motor symptoms in integrated care. In this report, we were integrating the holistic treatment with a case study. Case Report: Mr. J, who had a known history of Parkinson’ disease with severe motor symptoms. He showed tremendous improvement after integrated treatment was applied. More analytic research is needed in future to provide validation. Physiotherapy approaches: Balance training plays a vital role in reducing the risk of falls in individuals with PD. Evidence suggests that group exercises targeting mobility, coordination, and social interaction can positively impact individuals with PD. Stationary cycling, or pedaling, can have a positive impact on PD symptoms. Relaxation techniques, such as deep breathing, progressive muscle relaxation, and guided imagery have a high impact on patients. Evidence-based exercises targeting neck range of motion, neck muscle strengthening, and promotion of good posture. Conclusion: On the progression of the physiotherapy approaches and integrated care, Mr. J's performance in activities in daily living improved and he gained his confidence and independence.